FIELD EMERGENCE AND SEEDLING VIGOUR OF BREAD WHEAT AS INFLUENCED BY METHOD AND LONGEVITY OF STORAGE - Cheyed, S. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A laboratory experiment was carried out in the Seed Technology Laboratory, Department of Field Crop Sciences, College of Agricultural Engineering Sciences, University of Baghdad during the period 2010-2019. That was to evaluate bread wheat seeds stored in spikes in their field emergence and seedling vigour. Seeds, of stored spikes were compared with naked seeds, treated with cruise and untreated. All three treatments of seeds were grown in the laboratory and traits of days to last day of emergence, days to emerge, % of emergence, and other trails were recorded. Seeds of stored with thein spikes gave better values in days to last day of emergence, days of emergence, percent of emergence, length of plumule, seedling vigour and speed of emergence. The percent of emergence was decreased with increased years of storage, but those stored in their spikes were less affected. It was concluded that storing bread wheat with spikes had better results in field emergence as compared to seeds threshed and stored.